2016
DOI: 10.23953/cloud.ijanhs.140
|View full text |Cite
|
Sign up to set email alerts
|

Infant and Young Child-Feeding Practices, Indicators and Index, and Role of Socio-economic Status

Abstract: The present cross-sectional descriptive study was conducted at the paediatric OPD of a government and a private clinic to assess the indicators of Infant-and Young Child-feeding (IYCF) practices and compare them among lower middle and upper middle socioeconomic groups. The study enrolled 200 mother-child pairs with children aged 18-36 months, classified using Modified Kuppuswamy scale into Lower Middle Socioeconomic Group (LMSEG) (score: 11-15) and Upper Middle Socioeconomic Group (UMSEG) (score:16-25). IYCF i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A study conducted in Ghana showed that as the number of food groups consumed by mother increased, so too did the number consumed by their children (Amugsi, Mittelmark, & Oduro, ). Low socio‐economic status has been identified as a risk factor for low child dietary diversity in a wide range of contexts (Karwa, Godhia, & Jadhav, ; Rakotonirainy et al, ) and associations with stunted growth are well‐established (Adekanmbi, Kayode, & Uthman, ; Devakumar et al, ; Leroy, Habicht, Gonzalez de Cossio, & Ruel, ; Poda, Hsu, & Chao, ). Similarly, land ownership was also an important protective factor for child feeding practices in this study and others (Devakumar et al, ; Hailemariam, Girmay, & Girmay, ), perhaps due to the central role of agriculture in ensuring food security via food provision and/or income.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Ghana showed that as the number of food groups consumed by mother increased, so too did the number consumed by their children (Amugsi, Mittelmark, & Oduro, ). Low socio‐economic status has been identified as a risk factor for low child dietary diversity in a wide range of contexts (Karwa, Godhia, & Jadhav, ; Rakotonirainy et al, ) and associations with stunted growth are well‐established (Adekanmbi, Kayode, & Uthman, ; Devakumar et al, ; Leroy, Habicht, Gonzalez de Cossio, & Ruel, ; Poda, Hsu, & Chao, ). Similarly, land ownership was also an important protective factor for child feeding practices in this study and others (Devakumar et al, ; Hailemariam, Girmay, & Girmay, ), perhaps due to the central role of agriculture in ensuring food security via food provision and/or income.…”
Section: Discussionmentioning
confidence: 99%
“…This review highlighted studies suggesting the indicator of women's empowerment which facilitate IYCF practices. These facilitators are as follows: 1) Resources, includes sense of leadership [39], well-educated [13], [30], [31], [37], [42], [43], [48], and land ownership [48]; 2) Agency, includes involvement in household decision making process [42], [48]; and 3) Achievement, includes women stands against domestic violence [41], high socioeconomic status [30], [31], [37], [38], [48], and employment [31]. This review identified the indicators of women's empowerment from the resources dimension, which related to the good practice of IYCF by mother.…”
Section: Women's Empowerment As a Facilitator Of Iycf Practicesmentioning
confidence: 99%
“…At least, women should reach the finished secondary education level. As high as their level of education, their ability to perform a good IYCF practice is also increasing [13], [30], [31], [37], [42], [43], [48]. One study conducted in Ethiopia revealed that maternal land ownership had increased odds of dietary diversity score (DDS) among children 1.11 times [48].…”
Section: Women's Empowerment As a Facilitator Of Iycf Practicesmentioning
confidence: 99%
See 1 more Smart Citation